Kolaborasi Guru dalam MGMP Sebagai Peningkatan Mutu Pendidikan di MTs Unggulan Pondok Pesantren Amanatul Ummah Pacet Mojokerto - Afiyah Nur Kayati (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2020)
Abstract: Inter-teacher collaboration is one program that can improve teacher competency releasing. Teacher collaboration activities are channeled in the subject teachers' consultative forum or MGMP. Most MGMP activities are carried out at the sub-district, city or district level. However, not all teachers in one school join MGMP forums in sub-districts, cities, or districts, resulting in competency gaps between teachers of one subject in a school. MGMP forums at the school level need to be encouraged and carried out more routinely than MGMP activities to improve teacher professionalism in improving the quality of education in schools. This research is a qualitative research. The process of data acquisition is done by in-depth interview techniques, observation, and documentation related to the MGMP teacher collaboration activities in the MTs Unggulan PP Amanatul Ummah and their impact on the quality of learning in the classroom. Based on the results of the study it can be revealed that there are three forms of MGMP work meeting activities in the MTs Unggulan PP Amanatul Ummah. The most effective form of activity is the MGMP meeting for each subject. The program activities carried out include routine programs and development programs. MGMP teacher collaboration activities affect the improvement of the quality of education which is reflected in the increase in teacher competency and professionalism as well as improving the quality of learning.